2003
DOI: 10.1521/aeap.15.1.5.39.23613
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Partner Characteristics on HIV Infection Among African American Men Who Have Sex With Men in the Young Men's Survey, Los Angeles, 1999–2000

Abstract: Previous studies have documented disparities in HIV prevalence by race among men who have sex with men (MSM), even after adjusting for traditional risk factors. In this analysis of data collected for the 1999-2000 Los Angeles Young Men's Survey, a cross-sectional venue-based survey of MSM aged 23-29, we investigated whether information on male sex-partner characteristics accounts for some of the racial/ethnic differences in HIV prevalence. In this sample of survey participants, we observed that African America… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
194
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 189 publications
(205 citation statements)
references
References 19 publications
9
194
1
Order By: Relevance
“…13 Moreover, for Black MSM compared to White MSM, sexual partner choices (i.e., older age and having Black sexual partners) were better predictors of the higher rates of HIV seroprevalence in the sample than individual behavioral histories (i.e., HIV risk behavior). 13 Similarly, Berry and colleagues, in an analysis of data from the 2004 National HIV Behavioral Surveillance Survey in San Francisco, confirmed a significant tendency among Black MSM to have more partners of the same race. 24 Accordingly, a combination of intraracial and intergenerational sexual mixing may explain the disproportionate rates of HIV and STDs among Black MSM.…”
Section: Introductionmentioning
confidence: 89%
See 4 more Smart Citations
“…13 Moreover, for Black MSM compared to White MSM, sexual partner choices (i.e., older age and having Black sexual partners) were better predictors of the higher rates of HIV seroprevalence in the sample than individual behavioral histories (i.e., HIV risk behavior). 13 Similarly, Berry and colleagues, in an analysis of data from the 2004 National HIV Behavioral Surveillance Survey in San Francisco, confirmed a significant tendency among Black MSM to have more partners of the same race. 24 Accordingly, a combination of intraracial and intergenerational sexual mixing may explain the disproportionate rates of HIV and STDs among Black MSM.…”
Section: Introductionmentioning
confidence: 89%
“…Possible explanations for racial disparities in HIV and STD incidence have included socioeconomic position and cultural factors, structural barriers in accessing health care, and differences in sexual behavior. [7][8][9][10][11] Although studies have consistently found higher HIV prevalence among Black MSM relative to MSM of other races/ethnicities, comparable or lower rates of sexual risk behavior (i.e., unprotected anal sex [UAS]) have been observed among Black MSM compared to White and/or Latino MSM, 10,[12][13][14][15] suggesting that behavioral risk factors for HIV infection alone do not sufficiently explain elevated rates of HIV among Black MSM. 12 One potential explanation for higher HIV infection rates-that the sexual networks of Black MSM place them at greater risk for HIV and STDs than the sexual networks of other MSM-has not yet been sufficiently investigated.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations